LncRNA OIP5-AS1 promotes cell proliferation and migration and induces angiogenesis via regulating miR-3163/VEGFA in hepatocellular carcinoma. Issue 7 (2nd July 2020) - Shi, Changsheng; Yang, Qing; Pan, Songsong; Lin, Xingcheng; Xu, Gending; Luo, Ya; Zheng, Bingru; Xie, Xiangpang; Yu, Mingxu
ABSTRACT: Long noncoding RNAs (lncRNAs) have been reported to play a significant role in the occurrence and progression of tumors. In different tumors, they can either act as an oncogene or tumor suppressor via modulating various target mRNAs. OIP5-AS1 belongs to lncRNA family. It has been reported to be involved in the tumorigenesis of some cancers, such as bladder cancer, gastric cancer, and multiple myeloma. However, the role it plays in hepatocellular carcinoma (HCC) remains unclear. This study aims to explore the inherent mechanism of lncRNA OIP5-AS1 in HCC. In the first place, qRT-PCR found that OIP5-AS1 and VEGFA expressions were significantly increased while miR-3163 was obviously reduced in HCC cells and tissues. Next, a series of functional experiments found that knockdown of OIP5-AS1 suppressed HCC cell proliferation, migration and angiogenesis abilities while promoting cell apoptosis simultaneously. Last but not least, miR-3163 inhibition or VEGFA overexpression can reverse the anti-tumor effect of OIP5-AS1. In summary, OIP5-AS1 affects HCC proliferation, metastasis, and angiogenesis in HCC by regulating VEGFA expression through sponging miR-3163.